Ayat dan hadis Tentang Tauhid hubungannya dengan konsep pendidikan Islam Holisik - Mulyawan, Hafid; Mahmudi (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The aim of this research is to describe verses of the Qur’an and the hadiths about tauhid, and its relationship with the concept of holistic Islamic education. There are two objects in this research, such as described tauhid in the Qur’an and the Hadiths, and the holistic Islamic education. This research method using a qualitative method with a literature study approach. Tauhid in Arabic is one or single, so the meaning of tauhid is the unification of Allah and this is related to the aqidah or faith belief of Moslems, that Allah is only the one who is deserved to worship with all of His Greatness, Power and Perfection. Regarding the tawhid contained in the verses of Qur’an and the Hadiths which stating about prioritizing the purification of tauhid, it is important for Moslems to learn and to apply it. The application of tauhid education in Islamic education is a mandatory, because it is the most important part of Islamic religious education. Holistic Islamic education is a kind of Islamic education that develops all students potential in harmony, including intellectual, emotional, physical, social, aesthetic and spiritual. Holistic Islamic education is olso often called complete Islamic education.